Oral health status in relation to nutritional status among institutionalized autistic children and adolescents in Baghdad city, Iraq - Ali Hadi F.; Nada Jafer MH. Radhi (College of Dentistry/ University of Baghdad, 2017)
Background: The autism spectrum disorder (ASD) describes a wide range of symptoms, including difficulty with social interaction and communication skills. Controversial thinking about oral health of children with ASD, in general may have a lower hygiene level than healthy individuals, low caries rate and high body weight in comparison to healthy children. This study was conducted to assess the oral health status in relation to nutritional status among institutionalized autistic children and adolescents. Materials and methods: From 12 institutes in Baghdad, the study group contained 364 child and adolescent with ASD (Male= 294, Female=70), while control group included 441 normal child and adolescent (Male=357, Female=84) from primary and secondary schools. The age range (6-15) years old categorized to two age groups, children age group (6-10) years and adolescents age group (11-15) years. Decayed, missing and filled surfaces (dmfs, DMFS), plaque (PlI), Gingival (GI) and calculus (CI) indices were used to measure oral health status for both groups. Assessment of nutritional status performed by using BMI for age z-score value. The data of current study was analyzed using SPSS version 21. Results: Mean rank values of (dmfs, DMFS) were lower in study group than control group with high significant differences. The mean rank values of PlI, GI, and CI in study group were found to be higher than control group with high significant differences. A moderate positive high significant correlation was found between ds, dmfs, DS, DMFS and PlI, GI, CI in both groups. The mean rank values of body mass index (BMI) for age z-score were higher in study group than control group. Very weak negative high significant correlation between BMI for age z-score and ds, dmfs, DS, DMFS in study group. Conclusion: Dental caries severity, oral hygiene and gingival health were lower in ASD group than control group. Dental caries severity was related to oral health status in both groups. Possible of overweight, overweight and obesity were most common in children and adolescents with ASD than control group. Body weight of autistic children was related to dental caries severity.